2012
DOI: 10.1007/s00404-012-2369-4
|View full text |Cite
|
Sign up to set email alerts
|

Visual pain mapping in endometriosis

Abstract: In endometriosis patients, pain mapping to assess preoperative pain sensations relative to the anatomic location of endometriotic lesions is feasible. The pain provoked by vaginal examination is frequently perceived as median relative to the actual anatomic location of the endometriotic lesions. Several anatomic and neurophysiological factors may explain this phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 31 publications
0
10
0
3
Order By: Relevance
“…Evaluating the relationship between pain and endometriosis, however, is challenging given that pain is difficult to measure and the mechanism by which endometriosis causes pain is not well understood (American Society for Reproductive Medicine, 2014). While previous studies have provided important data on the incidence of pelvic pain and endometriosis (Cox et al, 2007;Kang et al, 2007;Ballard et al, 2010;Hsu et al, 2011;Renner et al, 2012), little research has been done to assess both the typology and topology of pelvic pain, and pain beyond the pelvis, and endometriosis diagnosis and severity using operative findings and a standardized classification system (American Society for Reproductive Medicine, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Evaluating the relationship between pain and endometriosis, however, is challenging given that pain is difficult to measure and the mechanism by which endometriosis causes pain is not well understood (American Society for Reproductive Medicine, 2014). While previous studies have provided important data on the incidence of pelvic pain and endometriosis (Cox et al, 2007;Kang et al, 2007;Ballard et al, 2010;Hsu et al, 2011;Renner et al, 2012), little research has been done to assess both the typology and topology of pelvic pain, and pain beyond the pelvis, and endometriosis diagnosis and severity using operative findings and a standardized classification system (American Society for Reproductive Medicine, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, endometriosis was confirmed in more than 80% of patients who underwent surgery. The extent of pain is not directly correlated with the location and extent of endometriosis 38 , 39 . Our data were unable to confirm an increase in rASRM scores for patients with significant clinical symptoms (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Auch in der vorliegenden Studie konnte bei über 80% der operierten Patientinnen eine Endometriose nachgewiesen werden. Grundsätzlich korreliert die Ausprägung der Schmerzsymptomatik nicht direkt mit der Lokalisation und Ausdehnung der Endometriose 38 , 39 . Auch unsere Daten können eine Zunahme des rASRM Scores bei ausgeprägter klinischer Symptomatik nicht bestätigen (data not shown).…”
Section: Diskussionunclassified
“…Untersuchungen zeigen, dass präoperativ zwar anhand der Schmerzen eine Lokalisation der Endometriose-Läsionen möglich ist (Renner et al, 2012), dies jedoch keinen Aufschluss über die Art der Endometriose gibt.…”
Section: In Anderen Studien Wurden Patientinnen Mit Tiefinfiltrierendunclassified